On the social desirability of centralized wage setting when fims are run by biased managers - Nicola Meccheri (Global Labor Organization (GLO), 2022)
This paper compares the welfare outcomes obtained under alternative unionization regimes (decentralized vs. centralized wage setting) in a duopoly market, in which shareholders delegate strategic decisions to biased (overconfident or underconfident) managers. In such a framework, the common tenet that consumer surplus and overall welfare are always higher under decentralized wage setting is completely overturned. Indeed, since in the presence of centralized unionization (industry-wide union) firms' shareholders always prefer to hire more aggressive or less conservative managers, output (consumer surplus) and overall welfare are larger in a centralized wage setting structure. This result holds true independently of the degree of product differentiation and the weight attached by unions to wages with respect to employment. Moreover, it also proves to be largely robust relative to the competition regime (quantity or price) in the product market.
Keywords: J51; L13; L22; 330; unionization structure; strategic delegation; biased managers; social welfare